Differential Effects of Temperature and Starvation on Induction of the Viable-but-Nonculturable State in the Coral Pathogens Vibrio shiloi and Vibrio tasmaniensis - Vattakaven, Thomas (American Society for Microbiology, 2006)
We compared induction of the viable-but-nonculturable (VBNC) state in two Vibrio spp. isolated from diseased corals by starving the cells and maintaining them in artificial seawater at 4 and 20°C. In Vibrio tasmaniensis, isolated from a gorgonian octocoral growing in cool temperate water (7 to 17°C), the VBNC state was not induced by incubation at 4°C after 157 days. By contrast, Vibrio shiloi, isolated from a coral in warmer water (16 to 30°C), was induced into the VBNC state by incubation at 4°C after 126 days. This result is consistent with reports of low-temperature induction in several Vibrio spp. A large proportion of the V. tasmaniensis population became VBNC after incubation for 157 days at 20°C, and V. shiloi became VBNC after incubation for 126 days at 20°C. Resuscitation of V. shiloi cells from cultures at both temperatures was achieved by nutrient addition, suggesting that starvation plays a major role in inducing the VBNC state. Our results suggest that viable V. shiloi could successfully persist in the VBNC state in seawater for significant periods at the lower temperatures that may be experienced in winter conditions, which may have an effect on the seasonal incidence of coral bleaching. For both species, electron microscopy revealed that prolonged starvation resulted in transformation of the cells from rods to cocci, together with profuse blebbing, production of a polymer-like substance, and increased membrane roughness. V. shiloi cells developed an increased periplasmic space and membrane curling; these features were absent in V. tasmaniensis.